Temporary migrants as an uneasy presence in immigrant societies: Reflections on ambivalence in Australia. (February 2019) - Tazreiter, Claudia
This article explores the status of temporariness in international migration. The focus is on the impact of temporary status on migrants' actions, behavior, and emotional responses to the daily circumstances in negotiating everyday life. Ambivalence is evaluated as an explanatory category that allows particular insight into strategies of resistance used by temporary migrants as they navigate a host society besides maintaining connections with home. Original data obtained from in-depth interviews with Indonesian migrant workers and students undertaking temporary migration projects in Australia is discussed. The case study explored in this article identifies some of the core problems temporary migrants face as encapsulated by a deficit of rights and protections that, at the same time, are expected by members of liberal states. Temporary status turns migrants into nomadic global laborers. The article argues that actions and responses that appear to be ambivalent are far from irrational, hasty, or disloyal. Rather, migrants' decision-making in response to the uncertain and shifting economic and sociocultural environments that they enter often comprises subtle calibrations and switching actions, observable as ambivalence, in adjusting to the unanticipated demands of a new society.